1998
DOI: 10.1073/pnas.95.10.5757
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a hepadnavirus from the woolly monkey, a New World primate

Abstract: Hepatitis B virus (HBV) infections are a major worldwide health problem with chronic infections leading to cirrhosis and liver cancer. Viruses related to human HBV have been isolated from birds and rodents, but despite efforts to find hepadnaviruses that infect species intermediate in evolution between rodents and humans, none have been described. We recently isolated a hepadnavirus from a woolly monkey (Lagothrix lagotricha) that was suffering from fulminant hepatitis. Phylogenetic analysis of the nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
1
8

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(184 citation statements)
references
References 16 publications
4
171
1
8
Order By: Relevance
“…1A). This host range difference was anticipated, since WMHBV does not efficiently infect chimpanzees in vivo (18). In spider monkey hepatocytes, WM-HDV particles showed a greater infectivity in the presence of PEG than they did in chimpanzee cells, and some infection was observed in the absence of PEG (Fig.…”
Section: Effect Of Peg On In Vitro Infection Of Hepatocytes With the mentioning
confidence: 96%
See 1 more Smart Citation
“…1A). This host range difference was anticipated, since WMHBV does not efficiently infect chimpanzees in vivo (18). In spider monkey hepatocytes, WM-HDV particles showed a greater infectivity in the presence of PEG than they did in chimpanzee cells, and some infection was observed in the absence of PEG (Fig.…”
Section: Effect Of Peg On In Vitro Infection Of Hepatocytes With the mentioning
confidence: 96%
“…Hepadnaviruses, like HBV, characteristically display very narrow host ranges that extend only to closely related species. The discovery and characterization of a nonhuman primate hepadnavirus from woolly monkeys confirmed the restrictions on the transmissibility of the virus between species, as chimpanzees were not susceptible to an efficient infection with woolly monkey hepatitis B virus (WMHBV) (18). However, analyses of the host range of WMHBV indicated that the host range extends to the close relative of the woolly monkey, the black-handed spider monkey; both primates are within the Atelidae family and the Atelinae subfamily.…”
mentioning
confidence: 98%
“…Since Thr-37, embedded in a sequence context favourable for O-glycosylation, is highly conserved in the pre-S2 domains of HBV genotypes B-F, in all primate hepatitis B virus genomes (Bartholomeusz & Schaefer, 2004) including the virus from the New World woolly monkey (Lanford et al, 1998) and even in the otherwise highly divergent pre-S2 sequence of WHV, respective threonine residues might be similarly glycosylated. The O-glycosylation at Thr-37 of pre-S2, however, cannot be essential for HBV genotype A, which exhibits no Thr within the range from aa 32 to 55, but contains numerous Ser residues in this region, which, as shown in this study, are not O-glycosylated.…”
Section: Discussionmentioning
confidence: 99%
“…1). In the woolly monkey hepatitis virus 63 and rodent hepatitis virus rt domain, there is length variability between conserved regions A and B, resulting in 346 and 342 amino acids for the respective rt domains (data not shown).…”
Section: Numbering Systems For Hiv-1 Polymerase and Hbv Surface Genementioning
confidence: 99%